Analysis of the relationship between the level of satisfaction with interpersonal relations in a dance couple, socio-psychological qualities of partners and the assessment of dyadic coping - V. A. Zirin; O. A. Ovsianik (Вестник университета, 2024)
The article presents the results of   studying the influence of  socio-psychological personality traits of   highly qualified dancers and their assessment of   dyadic coping on   the subjective level of   satisfaction with interpersonal relationships in  dance couples. The purposes of   the research are aimed at   identifying specific personality traits of   dancers and their coping strategies that have a   positive impact on  the process of   intraparty interpersonal communication. The research also involves an   empirical analysis and identification of   the features of   this influence. The following diagnostic tools have been used: the authors’ modified version of   the questionnaire of  satisfaction with marriage by   V.V. Stolin, T.A. Romanova and G.P. Butenko, the Dyadic Coping Inventory by   G. Bodenmann in  the adaptation of   T.L. Kryukova, O.A. Ekimchik and the five-factor personality questionnaire, 5PFQ, by   H. Tsuji in  the adaptation of   A.B. Khromov. Such socio-psychological personality qualities of  female dancers have been revealed as  extroversion, emotional stability, and practicality, which have the greatest influence on  subjectively high level of   satisfaction with relationships in  representatives of  both sexes. It  is stated that among all copings of  dyadic interaction delegated coping (in the direction of a  young man) and coping of   support from both partners impact the high level of   satisfaction with the existing interpersonal relations most. Further study of   the socio-psychological determinants of  interpersonal communication between all participants of   the dance and sports process is a   promising line of   research.